2000
DOI: 10.1103/physrevlett.84.51
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Excitation and Thermal Effects in Alkali-Halide Cluster Anions

Abstract: We have observed electronically excited states in alkali-halide cluster anions with one excess electron. Using photoelectron spectroscopy, we have found two narrow states in (KI)-2, (NaI)-2, and (NaCl)-2, consistent with a dipole-bound electron, while larger cluster anions exhibit a single broad excited state. In the larger systems, electronic excitation is often accompanied by vibrational excitation and thus a change in cluster temperature. Such temperature changes affect cluster structure and in some cases l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a previous study, on one-excess-electron AHCs, we attributed such broad absorptions to strong couplings between electronic and vibrational excitations [24] and found that those absorptions often lead to substantial heating or cooling of the clusters.…”
mentioning
confidence: 89%
“…In a previous study, on one-excess-electron AHCs, we attributed such broad absorptions to strong couplings between electronic and vibrational excitations [24] and found that those absorptions often lead to substantial heating or cooling of the clusters.…”
mentioning
confidence: 89%
“…Fatemi et al 123 used photoelectron spectroscopy to investigate the alkaline halide dimers (MX) 2 2 (M = Na, K; X = Cl, I). The spectra of these dimers show a relatively sharp single peak without notable vibrational progression, consistent with a linear C Hn chain arrangement.…”
Section: Some Recently Studied Dipole-bound Negative Ionsmentioning
confidence: 99%
“…3,14,15 Although reliable and informative, the experimental measurements cannot determine the geometrical structure of the anion or neutral species. In contrast, theoretical treatments, especially ab initio methods, are able to provide precise information about the origin of the electron binding by describing the potential responsible for it.…”
Section: Binding Of An Excess Electron To Sodium Chloridementioning
confidence: 99%